Design of web-based courses for secondary students - Michael Barbour (Flexible Learning Association of New Zealand, 2012)
This study considers the perceptions of course developers, teachers, and students on the characteristics of effective Web-based design for secondary school students. Through interviews and document analysis, the views of the participants on Web-based components, instructional strategies, and the effectiveness of both are investigated in a virtual high school context.